Modeling the distribution and neutralization processes of information influences in a social network segment - Улічев, Олександр Сергійович; Мелешко, Єлизавета Владиславівна (Ukrainian Information Security Research Journal, 2020)
In this paper, the research of existing social network generation models was conducted, the social network segment generation method was proposed with the possibility of choosing a different number and types of clusters, and distribution and neutralization processes of information influences in a social network segment with preselected network topology was simulated. The series of experiments to simulate the distribution and neutralization of information influences using various behavioral strategies by influence agents in a social network in order to identify the most effective actions for the dissemination of such influences was carried out. In total, three series of experiments were carried out. The first series of experiments to compare the effectiveness of the dissemination of information influences at various structural positions of influence agent in the social network segment was carried out. The second series of experiments in order to compare the effectiveness of informational influences with a different number of counteragents that counteract hostile informational influence was carried out. The third series of experiments at comparing the effectiveness of countering informational influence when blocking a different number of social connections of a hostile influence agent was carried out. It has been established that the effectiveness of information influences and information dissemination in a social network depends not only on the personal qualities of the influence agent, for example, his reputation, but also on the structural position and characteristics of nodes near influence agent. Experiments show that even with the most advantageous position and high potential of information impact, influence agent can be counteracted either by attracting counterparties or by blocking his social connections. The specific method of counteraction depends on the specific situation and the structure of the social network segment. A combined method can also be applied, when the spread of counter-information through counteragents is simultaneously used, and a certain number of social connections of influence agents are blocked.